Oscillating US Department of Defense policies and medical record documentation of gender dysphoria in service members: an observational time-series analysis - Krista B. Highland; David A. Klein; Sydney Rogers; Alexander G. Velosky; Christina Roberts; Noelle S. Larson (BMC, 2024)
Abstract Background United States military policies regarding service by transgender service members have shifted several times within the past decade. The relationships between policy changes and electronic health record documentation of gender dysphoria, a current and historic policy requisite for gender affirming care receipt, in active duty service members remain unknown. Methods Bayesian estimator of abrupt change, seasonality, and trend models identified changepoints in the proportion of service members who had new and then historical medical record documentation consistent with gender dysphoria from January 2015 to August 2022. Changepoints were evaluated as they related to salient military policy-related events. Results Approximately 3,853 active duty and activated National Guard or Reserve service members received a documented diagnosis corresponding to gender dysphoria from January 2015 to August 2022. Four significant changepoints were identified across both time series. Salient historical events that occurred during the changepoint periods were identified for contextualization. Conclusions Clinical documentation of gender dysphoria oscillated with changes to policies and public statements by government leaders, which may in turn, impact military recruitment and retention. This study highlights the need for equitable policies that optimize the strength of a diverse military force. Equity-oriented monitoring is needed to continually examine the impact of military service policies on readiness and retention to support actionable, data-driven improvements to policies and their implementation.